Penerapan Media Jenga for Question Card untuk Meningkatkan Pengetahuan dan Sikap Remaja Usia 16-18 Tahun tentang Sayuran dan Buah di SMAN 2 Bangkalan - Putri Zahrah Bakhtiar; Choirul Anna Nur Afifah (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2025)
The purpose of this study was to determine the application of jenga for question card media to improve knowledge and attitudes of 16-18 year old adolescents about vegetables and fruits at State Senior High School 2 Bangkalan. This type of research is quasi-experimental with a nonequivalent control group design. The sample in this study was 98 16-18 year old adolescents at State Senior High School 2 Bangkalan using non-random techniques. This study used a cooperative learning method with jenga for question cards. Respondents will take blocks on jenga if the respondent takes red then they will take a red question card and the respondent answers the question. Data on knowledge mastery of vegetable and fruit consumption were taken from multiple-choice tests and data on vegetable and fruit consumption attitudes using a Likert scale questionnaire. Because the data were not normally distributed, the data were analyzed by non-parametric statistics, namely Wilcoxon and Mann Whitney. The results showed that there was an increase in knowledge of 24 points and attitudes of 21.6 points after being given nutrition education.  The results of the bivariate test of the differences and effects of vegetable and fruit consumption nutrition education with jenga for question card media on the mastery of knowledge and attitudes have a p-value of 0.000. Vegetable and fruit consumption nutrition education with jenga for question card media has a significant effect on the mastery of Knowledge and Attitudes of 16-18 year old adolescents at State Senior High School 2 Bangkalan.